Kinetics of crude peroxidase inactivation from mangosteen (Garcinia mangostana L.) pericarp by using thermal treatment - Deylami, Mahsa Ziabakhsh; Abdul Rahman, Russly; Bakar, Jamilah; Olusegun, Lasekan; Tan, Chin Ping (Faculty of Engineering, Universiti Putra Malaysia, 2012)
Mangosteen (Garcinia mangostana L.) pericarp is a good source of phytochemicals that could be used as a valuable food ingredient. Blanching prior to further process can help to preserve phytochemicals. In this research, kinetics of crud peroxidase (POD) inactivation from mangosteen pericarp was investigated. Hot water blanching at temperature range of 70-100°C for 11min was applied. Kinetics of enzyme inactivation followed monophasic first-order model (R2=0.977-0.985) suggesting rapid inactivation of heat-labile fraction of the enzyme during the first seconds of treatment. The inactivation rate constant was 0.1189min-1 and 0.2424min-1 for 85℃ and 100℃, respectively. The activation energy (Ea) forperoxidase inactivation was 6699.9Jmol-1.The result of this work is a good tool to optimize thermal treatment of mangosteen pericarp.